Virtual competition. (Economist, 2008)
The article presents a profile of Diane Greene, Chief Executive Officer (CEO) of the computer software firm VMware. Greene's background as a naval architect and world windsurfing champion is given. Greene is a low-key personality who emphasizes the co-operative nature of computer software development, a stark contrast with the flamboyant, competitive executives who dominated the industry in the 1990s.